TINJAUAN PELAKSANAAN SISTEM PEMELIHARAAN REKAM MEDIS DI UPTD PUSKESMAS WANAYASA I KABUPATEN BANJANEGARA PROVINSI JAWA TENGAH - Harsono Harsono; Isnaini Qoriatul Fadhilah (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2021)
At the Wanayasa I Health Center UPTD, it was found that the medical record folder was torn so that the identity of the patient's medical record number could not be read and the officers often turned the folder over to view the contents of the medical record. Another factor is the lack of knowledge of medical record officers because their educational background is not a medical record graduate and has never attended training related to medical record management. The purpose of the study was to describe the implementation of the medical record maintenance system at the Wanayasa I Public Health Center UPTD. The type of research used was a qualitative descriptive study with a cross sectional approach. The results of the research on physical document maintenance systems for space management, do not use air conditioning, storage, use 2 wooden document racks, but should be replaced with filing cabinets or roll o'packs. Preventive materials, by carrying out activities to put camphor. There is no specific prohibition regarding the medical record maintenance system. Extrinsic factors are not in accordance with the theory. The document maintenance system for preventing document damage includes mountainous air with a temperature range of 18°-23°C which is quite good for preventing document damage. For fumigation, archival restoration and microfilm are not currently carried out but preventive measures should be taken